Lattice deformations at martensite-martensite interfaces in Ni-Al - Schryvers, D; Boullay, P; Kohn, R; Ball, J (2001)
The atomic configurations at macrotwin interfaces between microtwinned martensite plates in $Ni_{65}Al_{35}$ material are investigated using high resolution transmission electron microscopy (HRTEM). The observed structures are interpreted in view of possible formation mechanisms of these interfaces. A distinction is made between cases in which the microtwins, originating from mutually perpendicular \{110\} austenite planes, enclose a final angle larger or smaller than $90^{°}$, measured over the boundary. Two different configurations, one with crossing microtwins and the other with ending microtwins producing a step configuration are described. The latter is related with the existence of microtwin sequences with changing variant widths. Although both features appear irrespective of the material’s preparation technique, rapid solidification seems to prefer the step configuration. Depending on the actual case, tapering, bending and tip splitting of the small microtwin variants is observed. Sever lattice deformations and reorientations occur in a region of 5 – 10 nm around the interface while sequences of single plane ledges gradually bending the microtwins are found up to 50 nm away form the interface. These structures and deformations are interpreted in view of the need to accommodate any remaining stresses.